PERBANDINGAN DIMENSI BUDAYA KPK DAN POLRI - Ratu Laura M.B.P; Tb. Ronny Nitibaskara (Program studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Persada Indonesia YAI, 2021)
KPK and Polri are two organisations that have functions and authorities in eradicating corruption. Nevertheless there is a division of authority between the two organisations. The KPK aims to help create a government that is clean, authoritative and free of corruption. On the other hand, the police have the authority to carry out investigations of all types of criminal activity pursuant to the prevailing criminal laws and regulations. Although several articles have clearly regulated the duties and functions of each of these organisations, their authorities sometimes still do overlap and this often gives rise to conflict. The comparison of legal culture is one solution to reduce the conflict. Using the analysis of T Hall and Hofstede's cultural dimensions, it is known that there are many cultural differences between the two legal entities which indicate the strengths and weaknesses of each authority. The difference in legal culture between KPK chairmen also need to be considered because each leader comes from different ethnic group, as well aa their experience and past culture.